How differences in heavy civil project set-up practices impact performance - Yearsley, William S., author (Colorado State University. Libraries, 2007)
The life cycle of a construction project traditionally involves five phases: procurement, pre-construction planning, execution, closeout, and maintenance. The second phase, pre-construction planning is broad in nature yet vital to achieving a successful project. This study is unique in its focus on the contractors' perspective of pre-construction planning in the heavy civil sector. Data utilized was derived from a national survey developed specifically for this research. A mailed questionnaire was sent to 1,334 senior executives nationally, of whom 121 responded. Participants were asked to respond to questions about the individual characteristics of their companies including financial performance. They then responded to a series questions asking them to rate how often they practiced specific project set-up activities. Project set-up activities were categorized into groups from which composite variables were developed. These composite variables were utilized to study the relationships between how often certain project set-up activities were practiced and their contribution to over-all company performance expressed as profit margin (earnings before interest and tax or EBIT). Multiple-regression, factor analysis and frequency analysis were used for evaluating this data. The descriptive responses were utilized to evaluate differences in patterns of variance based on individual company characteristics. Hierarchical cluster analysis was utilized to assess these relationships. Only a partial relationship was found between how often certain project set-up activities were practiced and over-all performance. Project set-up activities concerning the identification of risk and opportunities accounted for the majority of the relationships found. Individual company characteristics did not significantly correlate to patterns of variance in performance and which activities were practiced. Supplementary analysis contrasting mean scores from high margin companies with lesser performing peers yielded differences in how often project set-up activities are practiced. This research provides insights as to which project set-up activities are most often practiced by top performing construction companies. These insights provide a guide for construction contractors to consider as they look toward planning future projects. While only partial correlations to over-all performance were found in this research the door has been opened for further study.
Keywords: civil engineering; research; standard deviation; polls and surveys; success; trends; audiences; engineers; bias; planning; variables; copyright; design; general contractors; bids